INTELLIGENT RECOMMENDER SYSTEM FOR STUDENT USING BAYES CLASSIFICATION ALGORITHM - Miss Nayan N. Khandekar (International Journal of Advance Engineering and Research Development (IJAERD), 2018)
With the advanced development of resource technology, more and more digital resources are available in Internet. To maintain college study material repository online as i propose a “Intelligent Recommender system for student using Bayes Classification Algorithms”. this system provides document classification as well as recommender system for college students. It helps staff to upload study material and students to get the study material by convenient way and allow to provide rating for every study material to re-rank the links of study material uploaded by the staff. Reranking concept increases the interest of the student as he will get what he wants easily and overcome the resource restriction problem by providing additional live recommender system to student by using educational search engine.